2000
DOI: 10.1073/pnas.180301597
|View full text |Cite
|
Sign up to set email alerts
|

Phase identity of the maize leaf is determined after leaf initiation

Abstract: The vegetative development of the maize shoot can be divided into juvenile and adult phases based on the types of leaves produced at different times in shoot development. Models for the regulation of phase change make explicit predictions about when the identity of these types of leaves is determined. To test these models, we examined the timing of leaf type determination in maize. Clones induced in transition leaf primordia demonstrated that the juvenile and adult regions of these leaves do not become clonall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 48 publications
8
41
0
Order By: Relevance
“…An even stronger phenotype is seen in ProSPL9:rSPL9 plants, in which the juvenile phase is lost (this work). Clonal analyses with maize have indicated that vegetative phase change is not conferred by the shoot apical meristem, but rather that phase identity is determined autonomously in each leaf primordium (Orkwiszewski and Poethig, 2000). Our results are consistent with this observation, as SPL9 is normally expressed in leaf primordia, and increasing SPL9 levels in leaf primordia by expression from the ANT promoter is sufficient to accelerate phase change.…”
Section: Plastochron Length and Phase Changesupporting
confidence: 89%
“…An even stronger phenotype is seen in ProSPL9:rSPL9 plants, in which the juvenile phase is lost (this work). Clonal analyses with maize have indicated that vegetative phase change is not conferred by the shoot apical meristem, but rather that phase identity is determined autonomously in each leaf primordium (Orkwiszewski and Poethig, 2000). Our results are consistent with this observation, as SPL9 is normally expressed in leaf primordia, and increasing SPL9 levels in leaf primordia by expression from the ANT promoter is sufficient to accelerate phase change.…”
Section: Plastochron Length and Phase Changesupporting
confidence: 89%
“…The metachromatic stain Toluidine blue O stains non-lignified cell walls of maize purple and lignified cell walls blue/green (Lawson and Poethig 1995;Orkwiszewski and Poethig 2000). Juvenile leaves did not exhibit lignification in any tissues except for the secondary walls of the xylem in the vascular bundles (Figs 8, 9, 12, 13) and some of the parenchyma cells in the midrib at the base of leaf 5 (Figs 14 and 15).…”
Section: Histochemistrymentioning
confidence: 98%
“…Samples were then dehydrated through an ethanol series and transferred into Citrisolv (Fisher Scientific, Pittsburgh, Pennsylvania USA) and slowly infiltrated with liquid paraffin over 3 d. Subsequently, samples were poured into plastic holders and solidified over crushed ice. Sections (4-6 µm) were cut on a rotary microtome (American Optical, Buffalo, New York USA), de-paraffinized in Citrisolv, rehydrated in an ethanol series, and stained with Toluidine Blue O, a metachromatic stain for cellulose and lignin (Lawson and Poethig 1995;Orkwiszewski and Poethig 2000). Photographs were obtained using an Olympus BX60 light microscope with an Olympus SC 35 mm camera (Tokyo, Japan).…”
Section: Leaf Morphology Anatomy and Tensile Strength Measurementsmentioning
confidence: 99%
See 2 more Smart Citations